Effects of Media composition on Asymbiotic Seed Culture of Vanda tessellata : An Approach to In vitro Conservation (Plant Tissue Culture and Biotechnology, 2020)
For initiation of seed germination and protocorm growth in Vanda tessellata (Roxb.) Hook. ex G. Don different media, namely Knudson’s C basal medium, modified Knudson’s C basal medium, Murashige and Skoog basal medium, Vacin and Went basal medium and Lindeman basal medium either alone or supplemented with vitamin or 0.1% peptone (w/v) were used. Vitamin mixture was consisted of nicotinic acid, pyridoxine and thiamine HCl at 1 : 1 : 10, respectively. For the initiation of germination, all the treatments exhibited promising results without showing significant variation. But the rate of survival of the germinated seedlings was remarkably low in all the basal media. Maximum survival rate of germinated seedlings was recorded in MS + 0.1% peptone. Necrosis of protocorms was a common phenomenon in all the treatments and 100% necrosis was recorded in LM basal medium and LM + vitamin. Addition of vitamin mixture and peptone in the basal media increased the rate of survival as well as differentiation of the germinated protocorms. Maximum rooted plantlets were recorded in VW + 0.1% peptonePlant Tissue Cult. & Biotech. 30(2): 285-295, 2020 (December)